2005
DOI: 10.1213/01.ane.0000158608.27411.a9
|View full text |Cite
|
Sign up to set email alerts
|

Intraarticular Patient-Controlled Regional Anesthesia After Arthroscopically Assisted Anterior Cruciate Ligament Reconstruction: Ropivacaine/Morphine/Ketorolac Versus Ropivacaine/Morphine

Abstract: This study showed the feasibility and efficacy of intraarticular patient-controlled regional analgesia technique for pain relief after anterior cruciate ligament reconstruction. The combination of intraarticular ropivacaine, morphine, and ketorolac was superior to control or to a combination of ropivacaine and morphine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 19 publications
0
33
0
3
Order By: Relevance
“…There are some studies concerning intraarticular bupivacaine or ropivacaine for relieving the postoperative pain of arthroplasty of the knees [21,25]. This study is, therefore, the first to show that intraarticular levobupivacaine is as effective as bupivacaine in pain relief to reduce postoperative VAS scores, to improve patient satisfaction, and to reduce hospital stay.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…There are some studies concerning intraarticular bupivacaine or ropivacaine for relieving the postoperative pain of arthroplasty of the knees [21,25]. This study is, therefore, the first to show that intraarticular levobupivacaine is as effective as bupivacaine in pain relief to reduce postoperative VAS scores, to improve patient satisfaction, and to reduce hospital stay.…”
Section: Discussionmentioning
confidence: 68%
“…However, the amount of the leak, if present, may be determined only by experimental studies. Another one is intraarticular catheter infection, which can be decreased by placement of sterile catheters [25,26]. It has been shown that local anesthetics not only serve as agents for pain control but possess antimicrobial activity as well [27].…”
Section: Discussionmentioning
confidence: 99%
“…34 Moreover, the main effect of ketorolac is to harness the production of prostaglandins. 35 It is shown that ropivacaine combined with morphine and ketorolac for pain relief after minor arthroscopic procedures were found to give a synergistic effect. 36 Our present study showed that intra-articular administration of 30 mg ketorolac has the main effect on pain reduction after surgery, so this would confirm the beneficial effects of combining ketorolac and ropivacaine because patients receiving this combination had significantly lower VAS pain scores, specifically on movement up to 24 hours postoperatively compared with ropivacaine alone.…”
Section: Discussionmentioning
confidence: 99%
“…332 It was shown that the addition of ketorolac to continuous intra-articular infusion of ropivacaine and morphine led to lower pain scores and less analgesic consumed after ACL reconstruction than when ketolorac was omitted. 333 Tenoxicam, 20 mg, has been used successfully both as a sole intra-articular analgesic and as an adjunct in combination therapy. 334,335 …”
Section: Intra-articular Nsaidsmentioning
confidence: 99%